The nonviolent Apocalypse: Revelation's nonviolent resistance against Rome - Meyers, Jeffrey D. (Lexington Books/Fortress Academic, 2021)
In The Nonviolent Apocalypse, Jeffrey D. Meyers argues that Revelation's famously violent visions are actually acts of nonviolent resistance to the Roman Empire. Using insights from biblical studies and scholarship on nonviolence, Meyers shows how Revelation both engages in and calls for acts of nonviolent resistance.